Functional polyaniline/multiwalled carbon nanotube composite as an efficient adsorbent material for removing pharmaceuticals from aqueous media. (1st September 2018) - Dutra, Flávia Viana Avelar; Pires, Bruna Carneiro; Nascimento, Tienne Aparecida; Borges, Keyller Bastos
Abstract: The composite polyaniline/multiwalled carbon nanotube (PAni/MWCNT, 1:0.1 w/w ) was developed with the intention of binding the adsorbent properties of two materials and using it to adsorb pharmaceuticals from aqueous media. PAni/MWCNT was characterized by scanning electron microscopy, thermogravimetry, infrared spectroscopy, pH at the point of zero charge, and the effect on the surface wettability of the material. As proof of concept, adsorption studies were carried out using meloxicam (MLX) as the pharmaceutical and it was evaluated as a function of pH, temperature, ionic strength, contact time and variation in concentration. Kinetics and isothermal models were applied to evaluate the mechanism of the adsorption process. The best MLX adsorption result was at pH 2 with 6 min of contact with PAni/MWCNT. The kinetics models that fitted the experimental data were pseudo-second order and Elovich and the kinetics model was the dual-site Langmuir–Freundlich. Both models suggest that the adsorption occurs by the chemical nature of the surface and in the pores of the energetically heterogeneous composite. The PAni/MWCNT presented an adsorption capacity of 221.2 mg g −1, a very good value when compared with the literature and can be used to remove pharmaceuticals from aqueous environments. Graphical abstract: Highlights: New composite based on PAni/MWCNT was synthesized by simple methodology. Efficient adsorbent for environmental and analytical processes. PAni/MWCNT can be applicable for removal of pharmaceutical from aqueous media. PAni/MWCNT showed potential for use in sample preparation.